New fossil evidence of the extinct opossum Lestodelphys juga from the Argentinian Pampas: Implications for species delimitation and morphological diversity - Suarez Gomez, Sandra Catalina (2025)
A new record (specimen MPS 150) of Lestodelphys is described, collected close to the Arrecifes River, San Pedro, Buenos Aires Province (Argentina), from Late Pleistocene deposits (Lujanian Age). It preserves a facial portion of the skull, including dentition. Although its dental measurements overlap with those of the extinct species Lestodelphys juga and the largest specimens of the extant species Lestodelphys halli, the specimen exhibits a distinctive combination of morphological traits that differ from L. halli (i.e., slight decrease in size from I2 to I5, more robust canine and anterior root of P3, P1 oblique, gap between P1 and P2, centrocrista more inflected labially, StC well developed in M1, and metacone anteroposteriorly compressed in M4). In addition, the disproportion between the skull size and its dentition mirrors the mandibular-dental mismatch observed in the holotype of L. juga, reinforcing its assignment to the extinct species as the most parsimonious interpretation. No specimen preserving cranial material has been attributed to Lestodelphys juga (other than specimen MACN-Pv 6408, which preserves a fragmentary maxilla with molars in addition to a fragmentary dentary with m3-4, and was tentatively referred to that species), increasing the relevance of the new material. Finally, in the context of this new record, we analyze the variability of the genus and discuss the diagnostic characters traditionally used to differentiate the two species. Among these, size has often been emphasized. However, we observed an overlap in dental measurements between L. juga and L. halli, indicating that size alone may not constitute a reliable diagnostic feature.